Pengaruh Etika Profesi terhadap Peningkatan Integritas Akuntan Publik di Indonesia (Jurnal Kendali Akuntansi, 2025)
This research aims to examine the influence of professional ethics on the improvement of public accountants’ integrity in Indonesia. Professional ethics is a crucial element in maintaining the quality and credibility of audited financial statements. The study employs a quantitative descriptive approach, with data collected through questionnaires distributed to public accountants across various Public Accounting Firms (KAP) in Indonesia. Data analysis was conducted using simple linear regression. The results reveal that professional ethics—including principles such as integrity, objectivity, competence, confidentiality, and professional behavior—have a significant effect on the integrity of public accountants. A determination coefficient of 57.4% indicates that more than half of the variation in integrity can be explained by the application of professional ethics. These findings emphasize the critical role of ethical practices in strengthening public trust and supporting the stability of the national financial system. This study contributes to the development of ethical oversight and professional conduct standards for public accountants in Indonesia.